Does the Shortage of Marriageable Women Induce the Trafficking of Women for Forced Marriage? Evidence From China - Xiong, Wanru (Violence against women, 2022)
This article examines whether a shortage of marriageable women induces trafficking of women for forced marriage in China as commonly expected. I assemble a data set of 1,215 transactions of women for forced marriage from 2010–2018 using court documents. My analysis suggests that the trafficking of women is not a direct consequence of the local shortage of marriageable women. The fundamental causes are entrenched patriarchal values as indicated by a high local sex ratio at birth, sex-specific internal migration, and the marriage squeeze endured by socially marginalized men in the context of a shortage of women in the population.